Gender-specific dual effects of physical activity on depression and mortality: a nine-year cohort study in Chinese adults aged 45 and above - Dan Shan; Dan Shan; Meina Yang; Meina Yang; Kunyan Zhou; Kunyan Zhou (Frontiers in Public Health)
BackgroundRegular participation in physical activity (PA) reduces all-cause mortality (ACM) in the general population. However, the effects of PA on depressed patients and potential gender-specific responses have not been fully elucidated. In this study, we aimed to investigate the role of PA on new-onset depression and ACM in Chinese adults aged 45 year and older, with particular emphasis on gender differences.MethodsThis was a longitudinal cohort study that took place over a nine-year period and featured 2,264 participants drawn from the China Health and Retirement Longitudinal Study (CHARLS). PA levels were categorized into quartiles using metabolic equivalents (MET; minutes/week), and depression was evaluated according to the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) scale. Specific relationships between PA, depression, and mortality were then investigated by applying multivariate logistic regression and Cox proportional hazards models.ResultsHighest quantile levels of PA were correlated with a 37% increase in the risk of new-onset depression in middle-aged (45–59 years) and older adults (>60 years). This association was predominantly influenced by a significant increase in the risk of mild depression (a score of 10–14 on the CESD-10) (odds ratio [OR]: 1.76; 95% confidence interval [CI]: 1.29–2.42, p < 0.001), with a more pronounced effect observed in women (OR: 1.83; 95% CI: 1.26–2.66, p = 0.002). A critical threshold for PA was identified at 4536 MET-minutes/week, beyond which the risk of depression increased significantly (p < 0.05). Conversely, higher levels of PA were linked to a 90% reduction in ACM (HR: 0.10; 95% CI: 0.02–0.44, p = 0.002), with the effect being more pronounced in men.ConclusionWhile PA reduces mortality, excessive activity may increase the risk of mild depression, particularly in women. These findings highlight the need for gender-specific PA guidelines that balance physical and mental health outcomes.